CD147 as a Novel Prognostic Biomarker for Hepatocellular Carcinoma: A Meta-Analysis - Peng, Fei (Biomed Res Int, 2017)
We conducted a meta-analysis to investigate the controversial association of CD147 expression with HCC prognosis and clinicopathological characteristics. Eight studies from PubMed (1966–2016), EMBASE (1980–2016), Cochrane Library (1996–2016), Web of Science (1945–2016), China National Knowledge Infrastructure (1982–2016), and Wanfang databases (1988–2016) were considered. The associations between CD147 expression and clinicopathological parameters and overall survival (OS) or DFS/RFS were reassessed using the meta-analysis for odds ratio (OR) or hazard ratio (HR) and 95% confidence interval (CI). CD147 expression was associated with DFS/RFS (HR = 3.26; 95% CI: 1.82–5.83; P < 0.0001) but not with OS (HR = 1.35; 95% CI: 0.56–3.29; P = 0.51). We also delved deeper into the association between median survival time and CD147 expression owing to significant heterogeneity and found significant differences between high and low CD147 expression groups with respect to median survival time. CD147 expression was closely associated with the TNM stage (OR = 0.18; 95% CI: 0.04–0.85; P = 0.03) and venous invasion (OR = 6.29; 95% CI: 1.70–23.20; P = 0.006). In contrast, there was no association between CD147 expression and tumor stage, cirrhosis, differentiation, lymph node metastasis, HBsAg, and serum AFP levels. Thus, CD147 expression is potentially closely related to HCC survival and associated clinicopathological parameters, paving the way for further research.